Board Battle - Jake Maddox (Stone Arch Books, 2014)
When a group of bullies decide they own the local skatepark, Conner and his best friend, Hannah, are forced to practice elsewhere. Conner and Hannah have to outsmart the bullies if they want to practice for the upcoming competition. Because in the end, the fight for the skatepark will come down to the ultimate battle of the boards.
Keywords: Sport Stories -- Sport Stories